2021
DOI: 10.1016/j.ijid.2020.11.184
|View full text |Cite
|
Sign up to set email alerts
|

A dramatic rise in serum ACE2 activity in a critically ill COVID-19 patient

Abstract: Endothelial cells express surface angiotensin-converting enzyme 2 (ACE2), the main receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that promotes the infection of endothelial cells showing activation and damage. Bronchoalveolar lavage fluid from coronavirus disease-2019 (COVID-19) subjects showed a critical imbalance in the renin-angiotensin-aldosterone system with the upregulated expression of ACE2. Recently, intravenous recombinant ACE2 was reported as an effective therapy in severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 14 publications
(16 reference statements)
5
66
0
2
Order By: Relevance
“…As described in the Introduction, only a few studies reported increased ACE2 levels in patients with SARS-CoV-2 infection and COVID-19 (Nagy et al ., 2021, Patel et al ., 2021). ACE2 concentrations are strongly related to ACE2 catalytic activity (Zhang et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the Introduction, only a few studies reported increased ACE2 levels in patients with SARS-CoV-2 infection and COVID-19 (Nagy et al ., 2021, Patel et al ., 2021). ACE2 concentrations are strongly related to ACE2 catalytic activity (Zhang et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed increased levels of angiotensin-converting enzyme 2 (ACE2) following SARS-CoV-2 infection (Patel et al, 2021), and a case report showed very high ACE2 levels in a critically ill COVID-19 patient (Nagy et al, 2021). ACE2 is a common binding site for both SARS-CoV and SARS-CoV-2 (Zhu et al, 2018, Hoffmann et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A case report recently described the increase of serum ACE2 in a COVID-19 patient presenting with ARDS [ 16 ].…”
Section: Ace2mentioning
confidence: 99%
“…In other recent studies, neither down- nor upregulation of ACE2 was observed in human cell lines infected with SARS-CoV-2 [ 228 , 229 , 280 ]. In COVID-19 patients, plasma levels and enzymatic activity of ACE2 were found increased [ 281 , 282 ] or not altered [ 278 , 283 , 284 ]. On the other hand, plasma levels of DPP4, the entry receptor for MERS-CoV, were reported to be decreased in COVID-19 patients [ 285 ] and in patients infected with MERS-CoV [ 286 ].…”
Section: The Roles Of Ace2 and Angiotensin II In Coronavirus-induced mentioning
confidence: 99%